Composite material for hardening of tillage machines working bodies containing titanium and chromium borides synthesized using SHS-process - Luzan, S. A.; Sidashenko, A. I.; Luzan, A. S. (Інститут металофізики ім. Г. В. Курдюмова НАН України, 2020)
The article presents results of the study of the developed composite material based on the powder of Ni–Cr–B–Si system modified with the composite material obtained using the process of self-propagating high-temperature synthesis (SHS) and contained titanium and chromium borides. The microstructure of composite material weld overlay coatings is a matrix material—PG-10N-01 alloy, where solid inclusions such as titanium diboride and chromium boride are uniformly distributed. As found, the composite material has high abrasive wear resistance and can be recommended for hardening of tillage machines working bodies.
Keywords: composite material; mechanical activation; SHS-process; overlay welding; wear resistance